Internationale organisationers virkningshistorie. Teoretiske og metodiske overvejelser - Christensen, Ivan Lind; Ydesen, Christian (Temp - tidsskrift for historie, 2015)
The Impact of International Organizations: Towards a Theoretical and Methodological Framework The overall aim of this article is to examine the theoretical and methodological challenges that arise from attempts to trace the impact of international organizations. Numerous research fields seem to be engaged in similar or related methodological questions, e.g. globalization studies, impact studies, comparative education, history of education, global history. The communication between these fields is, however, rather limited. The purpose of this article is therefore to develop, through an eclectic scan in these related research fields, a grammar of movement and impact that opens up the notion of transnational space as well as clarifying how this grammar is conducive to answering the methodological questions raised by this recent research agenda. In conclusion the article presents a manageable model based on the analytical discussions of impact, space and movement.